Extracurricular Settings as a Space to Address Sociopolitical Crises The Case of Discussing Immigration in Gender-Sexuality Alliances Following the 2016 U.S. Presidential Election - Poteat, V Paul (American educational research journal, 2019)
School-based extracurricular settings could promote dialogue on sociopolitical crises. We considered immigration discussions within Gender-Sexuality Alliances (GSAs), which address multiple systems of oppression. Among 361 youth and 58 advisors in 38 GSAs (19 in 2016-2017/Year 1; 19 in 2017-2018/Year 2), youth in Year 1 reported increased discussions from baseline throughout the remaining school year; differences were non-significant in Year 2. In both years, youth reporting greater self-efficacy to promote social justice, and GSAs with advisors reporting greater self-efficacy to address culture, race, and immigration discussed immigration more over the year (adjusting for baseline). In interviews, 38 youth described circumstances promoting or inhibiting discussions: demographic representation, open climates, critical reflection, fear or consequences of misspeaking, discomfort, agenda restrictions, and advisor roles